The influence of particle morphology on the dynamic densification of metal powders - Eakins,D; Chapman,D (AIP Conference Proceedings)
Powders are well known for their dispersive properties, which derive from the many dissipative processes that occur during densification. While numerous studies have been devoted to understand these processes over a wide range of initial densities, the influence of particle morphology has been for the large part overlooked. In this paper, we discuss a new research campaign at the Institute of Shock Physics, to systematically investigate the role of starting configuration on the dynamic densification of metal powders. Multi-target gun loading experiments have been performed on both stainless steel and copper powders of equiaxed-and fiber-shaped morphology. Frequency-shifted PDV was employed to measure the structure and velocity of the dynamic densification wave, to yield the crush strength of the various powders. We find that while the crush strength for the stainless steel powders is reasonably described by a modifiedWu-Jing model, this model underpredicts the densification stress for the copper powder.